Full-biodegradable PE wrapping film and preparation process thereof

By designing a fully biodegradable structure in the PE stretch film and using materials such as PHA, cellulose nanofibrils and algae powder, the problems of poor biodegradability and insufficient puncture and tear resistance of the traditional PE stretch film have been solved, achieving a faster Biodegradable and higher resistance properties.

CN119348267AActive Publication Date: 2025-01-24上海森韦得实业有限公司

Patent Information

Application Number
CN202411931945.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-24
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The traditional PE wrapping film has poor biodegradability, which leads to white pollution problems, and has insufficient puncture and tear resistance, which cannot meet the needs of large-scale applications.

Method used

The design of the full biodegradable PE wound film includes the outer layer, the middle and the inner layer, and the degradable parent grains are added in all layers. Treatment to improve the resistance of the bonding membrane, tear, and degradation.

Benefits of technology

It improves the puncture and tear resistance of PE stretch film and accelerates its biodegradation speed, allowing the stretch film to quickly decompose under natural conditions and reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the field of packaging materials, and particularly discloses a full-biodegradable PE wrapping film and a preparation process thereof. The full-biodegradable PE wrapping film comprises an outer layer, a middle layer and an inner layer which are attached in sequence, the outer layer is prepared from the following raw materials: No.1 LLDPE (Linear Low Density Polyethylene), LDPE, an anti-blocking agent, a slipping agent and degradable master batch; the middle layer is prepared from the following raw materials: No.2 LLDPE, LDPE, MLLDPE and degradable master batch; the inner layer is prepared from the following raw materials in percentage by weight: No.3 LLDPE (Linear Low Density Polyethylene), LDPE (Low Density Polyethylene), biodegradable tackifying master batch and degradable master batch; the degradable master batch is prepared from the following raw materials in parts by weight: 30 to 50 parts of PHA, 10 to 16 parts of cellulose nanofibril, 2 to 3.5 parts of algae powder, 1 to 2 parts of glycerol, 1 to 2 parts of foaming agent and 0.1 to 0.5 part of nucleating agent. The PE wrapping film has the advantages of being resistant to stretching, high in puncture resistance, easy to degrade, high in degradation speed and capable of being completely degraded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of packaging materials, and more specifically, to a fully biodegradable PE stretch film and a preparation process thereof. Background Art

[0002] Stretch film, also known as "stretch film", is a new type of self-adhesive wrapping packaging material. It is widely used in combined wrapping packaging of industrial products due to its excellent properties such as high tensile strength, large elongation, good self-adhesion, high transparency, strong protection and good cleanliness.

[0003] Stretch film is primarily made of PVC, EVA, and PE. PE stretch film, due to its high production efficiency, environmental adaptability, high quality, low price, and non-toxicity and odorlessness, is considered the leading development direction in stretch film production. Traditional PE stretch film suffers from poor biodegradability and is difficult to decompose. With its widespread adoption and use, white pollution has also emerged. With the demand for low-carbon living, biodegradable plastics are becoming increasingly popular. Currently, the two main biodegradable materials are photodegradable and biodegradable. Photodegradable plastics are limited to applications such as farmland cover because they are typically used only in areas with long sunshine hours and ample sunlight. The polyolefins used as the primary raw material for PE stretch film have a high molecular weight and are highly hydrophobic, making them very slow to biodegrade in nature. Furthermore, conventional PE stretch film has low longitudinal elongation and poor transverse strength, making it prone to rupture when wrapping sharp objects. Its poor puncture and tear resistance make it unsuitable for large-scale applications. Summary of the Invention

[0004] In order to improve the puncture resistance and tear resistance of PE film and increase the degradation rate of PE stretch film, the present application provides a fully biodegradable PE stretch film and a preparation process thereof.

[0005] In the first aspect, the present application provides a fully biodegradable PE stretch film, which adopts the following technical solution: A fully biodegradable PE stretch film, comprising an outer layer, a middle layer and an inner layer laminated in sequence; The outer layer comprises the following raw materials in weight percentage: 20-30% No. 1 LLDPE, 63-75% LDPE, 1-3% anti-blocking agent, 2-5% lubricant, and 2-3% degradation masterbatch; The middle layer comprises the following raw materials in weight percentage: 30-35% No. 2 LLDPE, 25-35% LDPE, 23-39% MLLDPE, and 1-2% degradation masterbatch; The inner layer comprises the following raw materials in weight percentage: 40-45% No. 3 LLDPE, 48-56% LDPE, 3-5% biodegradable tackifying masterbatch and 2-3% degradation masterbatch; The density of the No. 1 LLDPE is 0.92 g / cm 3 , melt index is 2.3g / 10min, density of No. 2 LLDPE is 0.918g / cm 3 , melt index is 2g / 10min, density of No. 3 LLDPE is 0.92g / cm 3 , melt index is 1g / 10min; The degradable masterbatch comprises the following raw materials in parts by weight: 30-50 parts of PHA, 10-16 parts of cellulose nanofibrils, 2-3.5 parts of algae powder, 1-2 parts of glycerol, 1-2 parts of foaming agent, and 0.1-0.5 parts of nucleating agent.

[0006] By adopting the above technical solution, the melt index of No. 1 LLDPE in the outer layer and the melt index of No. 2 LLDPE in the middle layer are relatively high, and are larger than the melt index of No. 3 LLDPE in the inner layer. The melt index gradually decreases from the outer to the inner. The melt index of the outer layer is relatively high, and it has higher fluidity during film making, is easier to be stretched and plastic, helps to improve production efficiency, helps to form a more uniform and smoother film layer, and can also improve the wear resistance, tensile resistance and tear resistance of the stretch film, enhance the protective effect of the outer layer on the stretch film, and the high melt index can form The middle layer has a higher melt index than the inner layer, which helps to bond the middle layer with the inner layer and outer layer, and improves the structural stability of the overall film layer. It can provide certain strength and toughness while maintaining good processing performance and fluidity. The lower melt index of the inner layer LLDPE means that the molecular chain movement ability is weaker, which helps to improve the strength and toughness of the stretch film, better withstand external impact and pressure, protect the package from damage, and improve the film's barrier properties to substances such as water vapor and oxygen.

[0007] Degradable masterbatch is added to the outer layer, middle layer and inner layer. The degradation masterbatch is made of cellulose nanofibrils, algae powder, PHA, etc. PHA is polyhydroxyalkanoate, a new type of biodegradable polymer material with physical and chemical properties similar to polymer plastics, and PHA has excellent biodegradability and thermal stability. It can be completely degraded in soil at a temperature of (25±3)°C within about 30 to 60 days, and the degradation rate is very rapid. The addition of foaming agent and nucleating agent can make PHA have uniformly distributed and uniform pores, and the nucleating agent can effectively improve the crystallinity of the material, so that the foamed material has strong tensile strength and impact strength, high toughness and tear resistance, and the interface between the nucleating agent and PHA can release many low potential energy points, which greatly increases the probability of bubble nuclei appearing, and finally the pores of the degradation masterbatch are increased, so the contact area with microorganisms is increased, and the degradation rate is increased; cellulose nanofibrils and algae powder It has a high specific surface area and reactive functional groups, which can interact with PHA molecular chains to form a co-crystallization or mechanical interlocking type of tight bond, thereby enhancing the interaction between the PHA molecular chains, forming more cross-linking points, and increasing the degree of cross-linking. In addition, cellulose nanofibrils have high strength and toughness and can be used as a reinforcing phase, evenly dispersed in the PHA matrix, and tightly combined between the PHA molecular chains to form a uniform reinforcement network, thereby improving the tensile strength, flexural strength and fracture toughness of the PHA degradation masterbatch. In addition, the active groups contained in the nanofibrils and algae powder are hydrophilic and can be attacked by microorganisms in the moisture in the soil, causing the microorganisms to adhere to the surface of the PE stretch film and begin to erode. At the same time, the degraded cellulose nanofibrils and algae powder produce a large number of holes and grooves on the surface and inside the PE stretch film, providing more adsorption sites for organisms, accelerating the rupture of the covalent bonds of the PE stretch film, and making the PE stretch film rapidly biodegradable.

[0008] Optionally, the preparation method of the degradation masterbatch is as follows: The cellulose nanofibrils were treated with oxygen plasma, then dispersed in deionized water to form a suspension with a concentration of 3-5 wt%, and freeze-dried to obtain a fiber matrix; Dissolve the algae powder, add glycerol, and mix well to prepare an impregnation solution. Soak the fiber matrix in the impregnation solution for 2-4 hours, take it out, dry it, and grind it to prepare a matrix powder. The base powder is mixed evenly with PHA, a foaming agent and a nucleating agent at 90-100° C., then foamed at 150-160° C. and 15-20 MPa for 5-6 minutes, and then crushed into powder to prepare a degradation masterbatch.

[0009] By adopting the above technical scheme, the cellulose nanofibrils are first treated with oxygen plasma to introduce carboxyl groups and the like on their surface, thereby increasing the surface roughness and enhancing the hydrophilicity. When the cellulose nanofibrils are immersed in the impregnation solution, they can react with the carboxyl groups, hydroxyl groups and the like in the algae powder, load the algae powder on the cellulose nanofibrils, and improve the loading fastness between the cellulose nanofibrils and the algae powder. The algae powder on the surface of the cellulose nanofibrils further increases the surface roughness of the cellulose nanofibrils, while glycerol can increase the lubricity of the matrix powder when mixed with PHA, a nucleating agent and a foaming agent. Glycerol can also produce hydrogen bonds with the algae powder and the cellulose nanofibrils, thereby enhancing the dispersibility of the prepared matrix powder in the PHA and improving the compatibility, thereby improving the mechanical strength and tensile strength. The degradation masterbatch formed by high-temperature foaming has a porous structure and a large surface area, which allows more water molecules and oxygen to contact the surface of the degradation masterbatch, and can absorb a large amount of water, making it easier for water and oxygen to penetrate into the interior of the degradation masterbatch, accelerating the hydrolysis process, increasing the reaction of microorganisms or enzymes, and accelerating biodegradation. Moreover, the surface of the degradation masterbatch obtained by foaming is relatively rough, which is convenient for the attachment and growth of microorganisms, providing more channels for microorganisms and enzymes, making it easier for them to enter the interior of the stretch film for degradation, and also helping to discharge degradation products, thereby further accelerating the biodegradation process. With the degradation of cellulose nanofibrils, algae powder and PHA, the molecular chains in the PE stretch film break, and water and microorganisms enter the interior, thereby accelerating degradation.

[0010] Optionally, the PHA is poly(3-hydroxybutyrate-co-4-hydroxybutyrate).

[0011] By adopting the above technical solution, the thermal degradation temperature is as high as about 230°C, and it has high thermal stability. The addition of a nucleating agent facilitates the wrapping of bubbles by P34HB during the foaming process. Therefore, the degradation masterbatch prepared by foaming has good thermal stability and is not easy to lose its porous structure during melting.

[0012] Optionally, polylactic acid fiber, sodium lauryl sulfate and gum arabic are further added to the suspension, stirred evenly and then freeze-dried, and the mass ratio of the polylactic acid fiber, sodium lauryl sulfate, gum arabic to the cellulose nanofibrils is 0.3-0.4:0.28-0.3:1.9-2:1.

[0013] By adopting the above-mentioned technical scheme, polylactic acid fibers and other raw materials are added to the suspension. The polylactic acid fibers and cellulose nanofibrils have different thicknesses. When mixed with the cellulose nanofibrils, they can be staggered and tightly blended, while retaining a large number of gaps, increasing the porosity, so that the fiber matrix has certain air permeability, and the polylactic acid fibers also have good degradation ability. The addition of polylactic acid fibers can also improve the tensile resistance and toughness of the fiber matrix. The addition of sodium lauryl sulfate and gum arabic can form bubbles in the suspension during stirring, and the fibers are evenly dispersed and tightly structured. The capillary foam technology generated by stirring gives the skeleton formed by the polylactic acid fibers and cellulose nanofibrils a high yield stress, which can successfully maintain the network structure of the foam. After freeze-drying, a lightweight and porous solid foam fiber matrix is ​​formed, which can improve the porosity in the degradation masterbatch, facilitate the attachment of microorganisms, and increase the degradation rate.

[0014] Optionally, the polylactic acid fiber is made by the following method: Dispersing diatom frustules and carboxymethylated Tremella fuciformis polysaccharide in DMF, ultrasonically dispersing at 60-75° C. for 3-5 hours, filtering, washing, and drying to obtain modified diatom frustules; The polylactic acid resin and the modified diatom frustules are uniformly mixed and melt-spun to obtain polylactic acid fibers. The mass ratio of the polylactic acid resin to the diatom frustules and the carboxymethylated tremella polysaccharide is 1:0.05-0.1:0.1-0.2.

[0015] By adopting the above technical scheme, the Tremella polysaccharide contains polysaccharides and proteins, and is carboxymethylated. The carboxymethyl functional group is introduced into the Tremella polysaccharide through a chemical reaction. The Tremella polysaccharide contains a large number of hydroxyl functional groups. Therefore, after the carboxymethylation modification, the hydroxyl functional groups are partially or completely converted into carboxymethyl functional groups, so that the Tremella polysaccharide contains carboxyl groups, and the Tremella polysaccharide rich in carboxyl groups is obtained; Diatom shell is a natural porous silica material with good thermal stability and a unique multi-level pore structure. Moreover, the surface contains highly active silanol groups, and there is a hydrogen bond effect in the molecule. Therefore, the Tremella polysaccharide rich in carboxyl groups can interact with the hydroxyl groups on the surface of the diatom shell, thereby making the diatom shell rich in carboxyl groups, and the carboxyl functional groups have high reaction activity. The carboxyl groups on the surface of the diatom frustules and the carboxyl groups in the unreacted carboxyl groups of the tremella polysaccharide can react with the polylactic acid resin to form chemical bonds, thereby improving the interfacial bonding strength, enhancing the tensile properties and impact load resistance of the polylactic acid fiber, and increasing the degradation rate. Therefore, on the one hand, the carboxyl groups on the surface of the carboxyl groups of the tremella polysaccharide may increase the hydrophilicity of the polylactic acid fiber, thereby facilitating the penetration of water molecules and the degradation process. On the other hand, as an inorganic filler, the carboxyl groups of the tremella polysaccharide may change the crystallization behavior and the distribution of the amorphous region of the polylactic acid, thereby affecting its degradation rate. Diatom frustules and carboxymethylated tremella polysaccharide are dispersed in PLA slices by melt spinning. The silanol groups on the surface of the diatom frustules can form hydrogen bonds with the carbonyl groups on the polylactic acid molecular chain, thereby improving the interaction between the diatom frustules and the polylactic acid resin. After spinning, polylactic acid ultrafine nanofibers are obtained.

[0016] Optionally, the opening agent is porous starch, and the preparation method of the porous starch is as follows: Starch, pectin, water and microcrystalline cellulose are mixed in a mass ratio of 80-90:2-4:45:5, kneaded at 90-95°C for 10-15 minutes to obtain a composite, kept at 160-165°C and 18-20 MPa for 5-6 minutes, released the pressure and crushed to obtain a foaming intermediate; The foaming intermediate is dispersed in acetonitrile to form an emulsion with a concentration of 1.5-2wt%, succinic acid is dispersed in acetonitrile, heated and stirred to dissolve, the emulsion is added, the temperature is raised to 75-80°C, the temperature is kept for 20-24 hours, the emulsion is cooled to 60-65°C, filtered, washed, and dried at 120-125°C. The mass ratio of the foaming intermediate to succinic acid is 1:2.5-3.

[0017] By adopting the above technical solution, the porous starch has a high specific surface area and a porous structure, which enables it to absorb and release oils and fats, and also has good dispersibility. During the production process of the stretch film, it can be evenly dispersed in the film to form tiny particles or holes, reducing the adhesion between plastic stretch films, improving the smoothness and openness, making the processing smoother, and the porous structure increases its contact area with the surrounding environment, thereby improving the degradation process.

[0018] Through mixing, the combined effects of mechanical shear, friction and heat are used to improve the compatibility of pectin and corn starch, promote deep contact, friction and interaction between pectin and starch molecular chains, thereby initiating esterification cross-linking and forming an esterified cross-linked structure, thereby enhancing the pore wall strength of the porous starch and improving its mechanical tolerance. It can also improve the pore uniformity of the porous starch and increase its pore wall thickness, so that the porous starch can better transmit, disperse and withstand compression force, and has good tensile strength and good rebound and cushioning properties; and because there are a large number of pore structures distributed in the starch-based foaming material system, the starch molecular chains in these structures contain a large number of free hydroxyl groups. Therefore, the free hydroxyl groups in the pore wall structure of the porous starch can establish hydrogen bonds with water molecules in the environment, so that the porous starch can actively adsorb water molecules from the air and exhibit good hygroscopicity.

[0019] The carboxyl group at one end of succinic acid undergoes an esterification reaction with the hydroxyl group in the porous starch and is chemically bonded to the surface of the porous starch, while the carboxyl group at the other end of succinic acid does not react. The carboxyl functional group has high reactivity, which helps to improve the bonding strength between the porous starch and the outer raw material matrix material. Moreover, the carboxyl functional group on the surface provides more attachment points and reaction sites for microorganisms, further promoting the degradation of microorganisms.

[0020] Optionally, the density of the LDPE is 0.924 g / cm 3 , melt index is 1.9g / 10min; The density of the MLLDPE is 0.918 g / cm 3 , the melt index is 1g / 10min.

[0021] By adopting the above technical solution, LDPE is used in the outer layer, middle layer and inner layer, which can make the stretch film have strong tear resistance and puncture resistance, while improving the haze and transparency, enhancing the fit with the packaging, and increasing the flatness of the stretch film and the packaging aesthetics; MLLDPE is used in the middle layer. MLLDPE has higher impact strength and tensile yield strength, so that the stretch film can better maintain its integrity when subjected to external forces, is not easy to break or deform, and has a consistent melt viscosity, which can make it easier to form and improve production efficiency.

[0022] Optionally, the foaming agent is selected from at least one of azodicarbonamide, sodium bicarbonate and zinc oxide; The nucleating agent is selected from at least one of boron nitride, lignin and calcium carbonate.

[0023] By adopting the above technical solution, using at least one of azodicarbonamide, sodium bicarbonate and zinc oxide as a foaming agent, the porosity of the degradation masterbatch can be increased and the pore size can be smaller, while using at least one of boron nitride and the like as a nucleating agent can improve the mechanical properties and foaming effect of the degradation masterbatch.

[0024] Optionally, the thickness ratio of the outer layer, the middle layer and the inner layer is 3:4:3.

[0025] By adopting the above technical solution, the outer layer, middle layer and inner layer of the stretch film are matched with an appropriate thickness ratio, making it easier to stretch the stretch film, reducing the difficulty of operation, improving packaging efficiency, and also playing a good buffering role, effectively absorbing external impact and protecting the packaged goods from damage.

[0026] Optionally, the lubricant is selected from polyethylene wax or oleamide; The biodegradable tackifying resin is selected from at least one of rosin resin, polymerized rosin, disproportionated rosin, rosin glycol ester, rosin glycerol ester, rosin pentaerythritol ester, terpene resin, polymerized terpene, and terpene-styrene resin.

[0027] By adopting the above technical solution, the lubricant in the outer layer can form a lubricating film on the stretch film, reducing the friction coefficient of the film, so that the stretch film can slide more easily between layers during packaging, transportation and storage, reducing resistance, improving overall operating efficiency, improving the smoothness of subsequent processing, and enhancing packaging operation efficiency.

[0028] The biodegradable tackifying resin used in the inner layer can significantly improve the adhesion of the inner layer of the stretch film to the packaging, ensuring that the stretch film fits tightly to the surface of the packaging and is not easy to fall off. This adhesion also helps maintain the stability and integrity of the packaging during transportation and storage, preventing damage or scattering due to loose packaging. In addition, the tackifying resin can enhance the tensile strength, wear resistance and chemical resistance of the stretch film, so that it can better withstand various external forces and environmental factors.

[0029] In a second aspect, the present application provides a preparation process for a fully biodegradable PE stretch film, which adopts the following technical solution: A process for preparing a fully biodegradable PE stretch film comprises the following steps: mixing, melting, and extruding granulation of a formulated amount of raw materials for an outer layer to produce an outer layer material; mixing, melting, and extruding granulation of a formulated amount of raw materials for a middle layer to produce a middle layer material; and mixing, melting, and extruding granulation of a formulated amount of raw materials for an inner layer to produce an inner layer material. The outer layer material, the middle layer material and the inner layer material are mixed according to a proportion, and then melt-cast into a film with a melting temperature of 180-200°C.

[0030] By adopting the above technical solution, the raw materials of each layer are first mixed and melt-granulated, which can facilitate the uniform mixing of the components of each layer, so that the layers of the prepared PE stretch film are more uniform and have better thickness uniformity.

[0031] In summary, this application has the following beneficial effects: 1. Since the present application adds degradation masterbatch to the outer layer, middle layer and inner layer that are bonded to each other, and the degradation masterbatch is made by foaming PHA, cellulose nanofibrils, algae powder, glycerin, etc. under appropriate temperature and pressure, the prepared degradation masterbatch has a large surface area, high porosity, high tensile strength and impact strength, and strong puncture resistance. In addition, the cellulose nanofibrils and algae powder make the degradation masterbatch more hydrophilic, which is more conducive to the attachment and binding of microorganisms. As the cellulose nanofibrils and algae powder decompose and degrade, the roughness of the degradation masterbatch increases, and a large number of holes or grooves are gradually generated on the surface and inside of the stretch film, which is more conducive to the progress of biodegradation and can enable the stretch film to gradually complete full biodegradation.

[0032] 2. In this application, polylactic acid fibers, sodium lauryl sulfate and gum arabic are preferably added to the suspension formed by cellulose nanofibrils. After being stirred evenly, bubbles are generated, which increases the porosity of the fiber matrix. Moreover, the polylactic acid fibers and cellulose nanofibrils are of different thicknesses. While being tightly combined, the air permeability and porosity are also increased, thereby increasing the attachment sites of microorganisms and accelerating the rate of biodegradation.

[0033] 3. In this application, it is preferred to prepare modified diatom frustules by mixing diatom frustules and carboxymethylated tremella polysaccharide, and utilize carboxymethylated tremella polysaccharide to interact with the hydroxyl groups in the diatom frustules to improve the binding force between the diatom frustules and polylactic acid, thereby enhancing the mechanical strength of the polylactic acid fiber. At the same time, in the preparation of polylactic acid fibers by melt spinning, carboxymethylated tremella polysaccharide can also improve its hydrophilicity and crystallinity, and improve the degradation rate and mechanical strength of the polylactic acid. DETAILED DESCRIPTION

[0034] The following examples further illustrate the present application in detail.

[0035] Preparation Example 1: (1) 16 g of cellulose nanofibrils were treated with oxygen plasma, then dispersed in deionized water to form a suspension with a concentration of 5 wt%, and freeze-dried at -65 °C for 36 h to obtain a fiber matrix. The cellulose nanofibrils were selected from Guangzhou Zelong Chemical Technology Co., Ltd., with a product number of ZR-19. The oxygen plasma treatment power was 45 W and the treatment time was 10 min. (2) 3.5 g of algae powder was dissolved in 30 g of deionized water, and 2 g of glycerol was added to prepare an impregnation solution. The fiber matrix was immersed in the impregnation solution for 4 h, taken out and dried at 60 ° C for 10 h, and crushed to obtain a matrix powder with a particle size of 20 μm. The algae powder was Spirulina powder selected from Shaanxi Sinuote Biotechnology; (3) The prepared matrix powder was mixed evenly with 50 g of PHA, 2 g of foaming agent, and 0.5 g of nucleating agent, and then foamed at 160 ° C and 20 MPa for 5 min, and then crushed into a powder with a particle size of 5 μm. The PHA was P34HB, selected from Shandong Yikeman, model P34HB-10, the nucleating agent was boron nitride, and the foaming agent was sodium bicarbonate.

[0036] Preparation Example 2: (1) 10 g of cellulose nanofibrils were treated with oxygen plasma, then dispersed in deionized water to form a suspension with a concentration of 3 wt%, and freeze-dried at -65 °C for 36 h to obtain a fiber matrix. The cellulose nanofibrils were selected from Guangzhou Zelong Chemical Technology Co., Ltd., with a product number of ZR-19. The oxygen plasma treatment power was 50 W and the treatment time was 5 min. (2) 2 g of algae powder was dissolved in 30 g of deionized water, and 1 g of glycerol was added to prepare an impregnation solution. The fiber matrix was immersed in the impregnation solution for 2 h, taken out and dried at 60 ° C for 10 h, and crushed to obtain a matrix powder with a particle size of 20 μm. The algae powder was Spirulina powder selected from Shaanxi Sinuote Biotechnology; (3) The prepared base powder was mixed evenly with 30 g of PHA, 1 g of foaming agent, and 0.1 g of nucleating agent, and then foamed at 150 ° C and 15 MPa for 6 min, and then crushed into a powder with a particle size of 5 μm. The PHA was P34HB, selected from Shandong Yikeman, model P34HB-10, the nucleating agent was calcium carbonate, and the foaming agent was azodicarbonamide.

[0037] Preparation Example 3: The difference from Preparation Example 1 is that cellulose nanofibrils, algae powder and glycerol are not added. 50g PHA, 2g foaming agent and 0.5g nucleating agent are mixed evenly, then foamed at 160°C and 20MPa for 5min, and then crushed into a powder with a particle size of 5μm. The PHA is P34HB, selected from Shandong Yikeman, model P34HB-10, the nucleating agent is boron nitride, and the foaming agent is sodium bicarbonate.

[0038] Preparation Example 4: The difference from Preparation Example 1 is that the impregnation solution made of algae powder and glycerol is not used for impregnation. (1) 16g of cellulose nanofibrils are treated with oxygen plasma and then dispersed in deionized water to form a suspension with a concentration of 5wt%, which is freeze-dried at -65℃ for 36h to obtain a fiber matrix. The cellulose nanofibrils are selected from Guangzhou Zelong Chemical Technology Co., Ltd., with a product number of ZR-19. The oxygen plasma treatment power is 45W and the treatment time is 10min. (2) The fiber matrix is ​​evenly mixed with 50g PHA, 2g foaming agent and 0.5g nucleating agent, and then foamed at 160℃ and 20MPa for 5min, and then crushed into a powder with a particle size of 5μm. PHA is P34HB, selected from Shandong Yikeman, with a model number of P34HB-10, the nucleating agent is boron nitride, and the foaming agent is sodium bicarbonate.

[0039] Preparation Example 5: The difference from Preparation Example 1 is that 16 g of cellulose nanofibrils, 3.5 g of algae powder, 2 g of glycerol, 50 g of PHA, 2 g of foaming agent, and 0.5 g of nucleating agent are mixed evenly, then foamed at 160°C and 20 MPa for 5 minutes, and then crushed into a powder with a particle size of 5 μm. The PHA is P34HB, selected from Shandong Yikeman, model P34HB-10, the nucleating agent is boron nitride, and the foaming agent is sodium bicarbonate.

[0040] Preparation Example 6: The difference from Preparation Example 1 is that no foaming agent and nucleating agent are added. The base powder is mixed evenly with 50g PHA at 100°C and then extruded and granulated at 160°C. The PHA is P34HB, selected from Shandong Yikeman, model P34HB-10.

[0041] Preparation Example 7: The difference from Preparation Example 1 is that in step (1), 6.4 g of polylactic acid fiber, 4.48 g of sodium lauryl sulfate and 30.4 g of gum arabic are further added to the suspension, stirred at 2000 rpm for 15 min and then freeze-dried, wherein the polylactic acid fiber is prepared by the following method: ① 10 g of diatom shells and 20 g of carboxymethylated tremella polysaccharide are dispersed in 100 ml of DMF, ultrasonically dispersed at 60°C for 5 h, filtered, washed with deionized water 5 times, and dried at 80°C to obtain modified diatom shells. The preparation method of diatom shells is as follows: diatoms are oxidized with 30% hydrogen peroxide solution for 12 h, placed in 1 mol / l hydrochloric acid solution for acidification for 24 h, washed with water 5 times, and calcined at 600°C in an oxygen atmosphere. The mixture was uniformly mixed with the modified diatom shells for 2 hours and ball milled at a speed of 120 r / min for 0.5 hours; ② 100 g of polylactic acid resin was evenly mixed with the modified diatom shells and melt-spun to obtain polylactic acid fiber. The spinning temperature was 185 ° C. The mass ratio of polylactic acid resin, diatom shells and carboxymethylated tremella polysaccharide was 1:0.1:0.2. The polylactic acid resin was selected from Total of Thailand with the product number LX930. The preparation method of carboxymethylated tremella polysaccharide was as follows: 20 g of tremella polysaccharide was soaked in 200 ml of 85% ethanol, 6.82 g of sodium hydroxide was added and reacted at 50 ° C for 2 hours, 6,8 sodium hydroxide and 18.9 g of monochloroacetic acid were added, and the reaction was carried out at 60 ° C for 6 hours. The pH was adjusted to 7 with acetic acid, 80% ethanol was added to obtain a precipitate, and the precipitate was dried at 45 ° C.

[0042] Preparation Example 8: The difference from Preparation Example 1 is that in step (1), 4.8g of polylactic acid fiber, 4.8g of sodium lauryl sulfate and 32g of gum arabic are added to the suspension, stirred at 2000rpm for 15min and then freeze-dried, wherein the polylactic acid fiber is prepared by the following method: ① 5g of diatom shells and 10g of carboxymethylated Tremella polysaccharide are dispersed in 100ml The modified diatom shells were prepared by ultrasonic dispersion in DMF at 75 ° C for 3 h, filtration, washing with deionized water for 5 times, and drying at 80 ° C to obtain modified diatom shells. The preparation method of diatom shells was as follows: the diatoms were oxidized with 30% hydrogen peroxide solution for 12 h, placed in a 1 mol / l hydrochloric acid solution for acidification for 24 h, washed with water 5 times, sintered at 600 ° C in an oxygen atmosphere for 2 h, and ball milled at a speed of 120 r / min for 0.5 h; ② 100 g of polylactic acid resin was mixed evenly with the modified diatom shells, and melt-spun to obtain polylactic acid fibers. The spinning temperature was 185 ℃, the mass ratio of polylactic acid resin, diatom shell and carboxymethylated tremella polysaccharide is 1:0.05:0.1, the polylactic acid resin is selected from Total of Thailand, the product number is LX930, and the preparation method of carboxymethylated tremella polysaccharide is as follows: 20g of tremella polysaccharide is soaked in 200ml of 85% ethanol, 6.82g of sodium hydroxide is added and reacted at 50℃ for 2h, 6,8 sodium hydroxide and 18.9g of monochloroacetic acid are added, and the reaction is carried out at 60℃ for 6h, the pH is adjusted to 7 with acetic acid, 80% ethanol is added to obtain a precipitate, and it is dried at 45℃.

[0043] Preparation Example 9: The difference from Preparation Example 7 is that sodium lauryl sulfate and gum arabic are not added.

[0044] Preparation Example 10: The difference from Preparation Example 7 is that polylactic acid fiber is not added.

[0045] Preparation Example 11: The difference from Preparation Example 7 is that no diatom frustules and carboxymethylated tremella polysaccharide are added to the polylactic acid fiber, and the polylactic acid fiber is only made of polylactic acid resin by melt spinning.

[0046] Preparation Example 12: The difference from Preparation Example 7 is that diatom frustules are used in an equal amount to replace carboxymethylated Tremella polysaccharide in the polylactic acid fiber.

[0047] Preparation Example 13: The difference from Preparation Example 7 is that the Tremella polysaccharide is not subjected to carboxymethylation treatment.

[0048] Preparation Example 14: 90 g of corn starch, orange pectin, deionized water, and microcrystalline cellulose in a mass ratio of 90:2:45:5 were mixed and kneaded at 95° C. for 10 min to prepare a composite, which was then kept at 165° C. and 18 MPa for 6 min, released, and pulverized to prepare a porous starch.

[0049] Preparation Example 15: 90 g of corn starch, orange pectin, deionized water, and microcrystalline cellulose in a mass ratio of 90:2:45:5 were mixed and kneaded at 95° C. for 10 minutes to prepare a composite. The composite was then kept at 165° C. and 18 MPa for 6 minutes, depressurized, and crushed to prepare a foaming intermediate. Disperse 10 g of the foaming intermediate in acetonitrile to form an emulsion with a concentration of 2 wt%. Disperse 30 g of succinic acid in 500 ml of acetonitrile, heat and stir to dissolve, add the emulsion, heat to 75 ° C, keep warm for 24 hours, cool to 65 ° C, filter, wash with anhydrous ethanol and deionized water three times each, and dry at 120 ° C. The mass ratio of the foaming intermediate to succinic acid is 1:3.

[0050] Preparation Example 16: Corn starch, orange pectin, deionized water, and microcrystalline cellulose were mixed in a mass ratio of 80:2:45:5 and kneaded at 95°C for 10 minutes to prepare a composite. The composite was then kept at 160°C and 20 MPa for 5 minutes, depressurized, and crushed to prepare a foaming intermediate. Disperse 10 g of the foaming intermediate in acetonitrile to form an emulsion with a concentration of 1.5 wt%. Disperse 25 g of succinic acid in 500 ml of acetonitrile, heat and stir to dissolve, add the emulsion, heat to 80 ° C, keep warm for 20 hours, cool to 60 ° C, filter, wash with anhydrous ethanol and deionized water three times each, and dry at 125 ° C. The mass ratio of the foaming intermediate to succinic acid is 1:2.5. Example

[0051] Example 1: A fully biodegradable PE stretch film, comprising an outer layer, a middle layer, and an inner layer laminated in sequence with a mass ratio of 3:4:3, and the raw material proportions of the outer layer, the middle layer, and the inner layer are shown in Table 1. The melt index (190°C, 2.16 kg) of No. 1 LLDPE in the outer layer is 2.3 g / 10 min, and the density is 0.92 g / cm 3 , selected from Liaotong Chemical, brand LL0220AA, density of No. 2 LLDPE is 0.198g / cm 3 , melt index (190℃, 2.16kg) is 2g / 10min, selected from Exxon, brand is 1002BU, density of No. 3 LLDPE is 0.92g / cm 3 The melt index (190℃, 2.16kg) is 1g / 10min, selected from Dow Chemical of the United States, the brand is 2045G, and the density of LDPE is 0.925g / cm 3 The melt index (190℃, 2.16kg) is 1.9g / 10min, selected from CNOOC Shell, the brand is 2420H, and the density of MLLDPE is 0.918g / cm 3 , the melt index (190℃, 2.16kg) is 1g / 10min, the brand is DowDuPont, the brand is 5401G, the opening agent is erucamide, the lubricant is polyethylene wax, the biodegradable tackifying masterbatch is rosin resin, and the degradable masterbatch is made by Preparation Example 1.

[0052] The preparation process of the above-mentioned fully biodegradable PE stretch film comprises the following steps: According to the raw material amounts in Table 1, the outer layer raw materials were mixed, melted at 160°C, and granulated to obtain the outer layer material; the middle layer raw materials were mixed, melted at 160°C, and granulated to obtain the middle layer material; the inner layer raw materials were mixed, melted at 160°C, and granulated to obtain the inner layer material; The outer layer material, the middle layer material and the inner layer material are mixed according to the ratio, and then melt-cast into a film to obtain a stretch film with a thickness of 19 μm. The melting temperature is 180°C, the casting roller speed is 1.2 m / min, the pulling roller speed is 1.4 m / min, the pulling roller synchronization coefficient is 1.2, the winding roller tension is 2.8 kg, the winding roller synchronization coefficient is 0.4, and the cooling roller temperature is 30°C.

[0053] Table 1 Raw material dosage of fully biodegradable PE stretch film in Examples 1-3

[0054] Example 2: A fully biodegradable PE stretch film. The difference from Example 1 is that the raw material proportions of the outer layer, middle layer and inner layer are as shown in Table 1, and the degradation masterbatch is made from Preparation Example 2.

[0055] The preparation process of the above-mentioned fully biodegradable PE stretch film comprises the following steps: According to the raw material amounts in Table 1, the outer layer raw materials were mixed, melted at 170°C, and granulated to obtain the outer layer material; the middle layer raw materials were mixed, melted at 170°C, and granulated to obtain the middle layer material; the inner layer raw materials were mixed, melted at 170°C, and granulated to obtain the inner layer material; The outer layer material, the middle layer material and the inner layer material are mixed according to the ratio, and then melt-cast into a film to obtain a stretch film with a thickness of 19 μm. The melting temperature is 200°C, the casting roller speed is 0.8 m / min, the pulling roller speed is 1.1 m / min, the pulling roller synchronization coefficient is 1.5, the winding roller tension is 3.5 kg, the winding roller synchronization coefficient is 0.4, and the cooling roller temperature is 20°C.

[0056] Example 3: A fully biodegradable PE stretch film, which differs from Example 1 in that the raw material proportions of the outer layer, middle layer, and inner layer are as shown in Table 1.

[0057] Example 4: A fully biodegradable PE stretch film, which differs from Example 1 in that the biodegradable masterbatch in the outer layer, middle layer and inner layer is made from Preparation Example 7.

[0058] Example 5: A fully biodegradable PE stretch film, which differs from Example 1 in that the biodegradable masterbatch in the outer layer, middle layer and inner layer is made from Preparation Example 8.

[0059] Example 6: A fully biodegradable PE stretch film, which differs from Example 4 in that the biodegradable masterbatch in the outer layer, middle layer and inner layer is made from Preparation Example 9.

[0060] Example 7: A fully biodegradable PE stretch film, which differs from Example 4 in that the biodegradable masterbatch in the outer layer, middle layer and inner layer is made from Preparation Example 10.

[0061] Example 8: A fully biodegradable PE stretch film, which differs from Example 4 in that the biodegradable masterbatch in the outer layer, middle layer and inner layer is made from Preparation Example 11.

[0062] Example 9: A fully biodegradable PE stretch film, which differs from Example 4 in that the biodegradable masterbatch in the outer layer, middle layer and inner layer is made from Preparation Example 12.

[0063] Example 10: A fully biodegradable PE stretch film, which differs from Example 4 in that the biodegradable masterbatch in the outer layer, middle layer and inner layer is made from Preparation Example 13.

[0064] Example 11: A fully biodegradable PE stretch film, which differs from Example 4 in that the opening agent in the outer layer is porous starch, and the porous starch is prepared by Preparation Example 14.

[0065] Example 12: A fully biodegradable PE stretch film, which differs from Example 4 in that the opening agent in the outer layer is porous starch, and the porous starch is prepared according to Preparation Example 15.

[0066] Example 13: A fully biodegradable PE stretch film, which differs from Example 4 in that the opening agent in the outer layer is porous starch, and the porous starch is prepared by Preparation Example 16.

[0067] Comparative Example 1: A fully biodegradable PE stretch film, which differs from Example 1 in that the degradation masterbatch is made from Preparation Example 3.

[0068] Comparative Example 2: A fully biodegradable PE stretch film, which differs from Example 1 in that the degradation masterbatch is prepared from Preparation Example 4.

[0069] Comparative Example 3: A fully biodegradable PE stretch film, which differs from Example 1 in that the degradation masterbatch is made from Preparation Example 5.

[0070] Comparative Example 4: A fully biodegradable PE stretch film, which differs from Example 1 in that the degradation masterbatch is made from Preparation Example 6.

[0071] Comparative Example 5: A fully biodegradable PE stretch film. The difference from Example 1 is that No. 1 LLDPE is used in the inner layer instead of No. 3 LLDPE. The melt index (190°C, 2.16 kg) of No. 1 LLDPE is 2.3 g / 10 min and the density is 0.92 g / cm 3 , selected from Liaotong Chemical, brand LL0220AA.

[0072] Comparative Example 6: A fully biodegradable PE stretch film, which differs from Example 1 in that No. 1 LLDPE is replaced by No. 3 LLDPE in the outer layer, and the density of No. 3 LLDPE is 0.92 g / cm 3 , the melt index (190℃, 2.16kg) is 1g / 10min, selected from Dow Chemical of the United States, the brand is 2045G.

[0073] PE stretch films were prepared according to the methods in the examples and comparative examples, and performance tests were performed according to the following methods. The test results are recorded in Table 2.

[0074] 1. Tensile strength and elongation at break: The test was conducted in accordance with GB / T 1040.3-2006 "Determination of tensile properties of plastics - Part 3: Test conditions for film and sheeting" at a measuring speed of 10 mm / s. Three groups of tests were performed for each embodiment or comparative example, and the average value was taken.

[0075] 2. Impact strength: Tested in accordance with GB / T1843-2008, the test speed is 3.5m / s, 3 groups of tests are performed, and the average value is taken.

[0076] 3. Water absorption rate: Cut the film into 2 cm × 2 cm pieces and place it in 30 mL of distilled water at room temperature until the film completely absorbs the water. Use absorbent paper to dry the surface moisture of the film and weigh it. Test the mass before and after water absorption and calculate the water absorption rate.

[0077] 4. Biodegradation Test: The test was conducted using the natural soil landfill method. A 10g sample (10mm x 10mm) was placed in a 100mm x 100mm x 100mm pit, with the sample 10mm away from the soil. The soil used was loose farmland with a pH of 6-8 and a humidity level >80%. The test was conducted outdoors. After various landfill times, the weight of the remaining sample was measured to determine its biodegradability. Weight loss (%) = (initial sample mass - remaining sample mass) / initial sample mass × 100.

[0078] Table 2 Performance test of fully biodegradable PE stretch film

[0079] Combining the data in Table 2 with the raw material selection in Examples 1-3, it can be seen that the PE stretch films prepared in Examples 1-3 using the degradation masterbatches prepared in Preparation Example 1 and Preparation Example 2 have strong initial tensile strength and puncture resistance, high water absorption, and good biodegradability. They can be degraded by more than 90% within 12 weeks, with a fast degradation rate, and can be completely degraded over time.

[0080] Compared with Example 1, Example 4 and Example 5 respectively use the degradation masterbatch prepared in Preparation Example 7 and Preparation Example 8. Compared with Example 1, Preparation Example 7 and Preparation Example 8 also add polylactic acid fiber, sodium lauryl sulfate and gum arabic to the fiber matrix. It can be seen that the mechanical strength of the prepared PE stretch film is increased, and the impact resistance and tear resistance are enhanced. In addition, the water absorption rate is increased, it is more hydrophilic, easier to degrade, and the biodegradation rate is increased.

[0081] Compared with Example 4, Example 6 uses the degradation masterbatch prepared in Preparation Example 9. Compared with Preparation Example 8, Preparation Example 9 does not add sodium lauryl sulfate and gum arabic. Table 2 shows that the PE stretch film prepared in Example 6 has a lower water absorption rate and a lower degradation rate, indicating that freeze-drying of sodium lauryl sulfate and gum arabic after stirring can increase the bubble content, improve the porosity in the fiber matrix, and thus enhance the water absorption rate and improve the degradation rate.

[0082] Compared with Example 4, Example 7 uses the degradation masterbatch prepared in Preparation Example 10, in which no polylactic acid fiber is added. It can be seen that the tensile strength and impact strength of the PE stretch film made therefrom are significantly reduced, and the water absorption rate is reduced, and the biodegradation rate is slowed down.

[0083] In Example 8, the degradation masterbatch prepared in Preparation Example 11 was used. Compared with Preparation Example 7 in Example 4, diatom frustules and carboxylated tremella polysaccharide were not added to the polylactic acid fiber in Preparation Example 11. It can be seen that the tensile and puncture resistance of the PE wrapping film prepared in Example 8 were reduced, and the degradation rate was slowed down, indicating that the addition of diatom frustules and carboxymethylated polysaccharides to the polylactic acid fiber can improve the crystallinity of polylactic acid, enhance the tensile strength of the polylactic acid fiber, and increase the degradation rate.

[0084] In Example 9, the degradation masterbatch prepared in Preparation Example 12 was used. Compared with Example 4, diatom frustules were used instead of carboxymethylated tremella polysaccharide in Preparation Example 12, while in Example 10, the degradation masterbatch prepared in Preparation Example 13 was used, in which tremella polysaccharide was not carboxymethylated. It can be seen that in the PE stretch film materials prepared in Examples 9 and 10, the amount of diatom frustules in Example 9 was increased. Although the degradation rate of the PE stretch film increased, it had an adverse effect on the tensile strength of the polylactic acid fiber, etc., resulting in a decrease in the mechanical strength of the PE stretch film. In Example 10, the mechanical strength and mixed water absorption rate of the stretch film did not change much, but the degradation rate slowed down.

[0085] In Example 11, the porous starch prepared in Preparation Example 14 is used as an opening agent. The porous starch is made of corn starch, orange pectin, etc. through heat preservation and foaming. Compared with the use of erucamide in Example 4, the water absorption rate of the PE wrapping film is slightly improved, and the degradation rate is increased.

[0086] Compared with Example 4, Example 12 and Example 13 respectively use the porous starch prepared in Preparation Example 14 and Preparation Example 15 as the opening agent, and use succinic acid to modify the porous starch. The degradation ability of the PE stretch film prepared in Example 12 and Example 13 is further enhanced.

[0087] In Comparative Example 1, the degradation masterbatch prepared in Preparation Example 3 was used. Compared with Preparation Example 1, cellulose nanofibrils and algae powder were not added. PHA was blended with a foaming agent and a nucleating agent for foaming. It can be seen that the tensile properties of the PE wrapping film deteriorated, the water absorption rate decreased, and the degradation rate slowed down.

[0088] In Comparative Example 2, the degradation masterbatch prepared in Preparation Example 4 was used. Compared with Example 1, algae powder and glycerol were not used to soak the fiber matrix. In Comparative Example 3, the degradation masterbatch prepared in Preparation Example 5 was used. Compared with Preparation Example 1, cellulose nanofibrils were blended and foamed with PHA, etc. As shown in Table 2, the tensile strength of the PE stretch films prepared in Comparative Examples 2 and 3 did not change much, but the water absorption rate decreased and the degradation rate slowed down.

[0089] Comparative Example 4 uses the degradation masterbatch prepared in Preparation Example 6. Compared with Preparation Example 1, no foaming agent and nucleating agent are added. Compared with Example 1, the tensile strength and elongation at break of the PE stretch film prepared in Comparative Example 4 are reduced, the impact strength is weakened, the water absorption rate is significantly reduced, and the degradation rate is slowed down.

[0090] Compared with Example 1, Comparative Examples 5 and 6 respectively change the melt index of LLDPE in the inner layer and the outer layer. It can be seen that the tensile strength and other properties of the PE stretch film are reduced, and the puncture resistance is weakened.

[0091] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A fully biodegradable PE stretch film, characterized in that: It includes an outer layer, a middle layer and an inner layer which are laminated in sequence; The outer layer comprises the following raw materials in weight percentage: 20-30% No. 1 LLDPE, 63-75% LDPE, 1-3% anti-blocking agent, 2-5% lubricant, and 2-3% degradation masterbatch; The middle layer comprises the following raw materials in weight percentage: 30-35% No. 2 LLDPE, 25-35% LDPE, 23-39% MLLDPE, and 1-2% degradation masterbatch; The inner layer comprises the following raw materials in weight percentage: 40-45% No. 3 LLDPE, 48-56% LDPE, 3-5% biodegradable tackifying masterbatch and 2-3% degradable masterbatch; The density of the No. 1 LLDPE is 0.92 g / cm 3 , the melt index is 2.3g / 10min, and the density of No. 2 LLDPE is 0.918g / cm 3 , the melt index is 2g / 10min, and the density of No. 3 LLDPE is 0.92g / cm 3 , melt index is 1g / 10min; The degradable masterbatch comprises the following raw materials in parts by weight: 30-50 parts of PHA, 10-16 parts of cellulose nanofibrils, 2-3.5 parts of algae powder, 1-2 parts of glycerol, 1-2 parts of foaming agent, and 0.1-0.5 parts of nucleating agent.

2. The fully biodegradable PE stretch film according to claim 1, characterized in that: The preparation method of the degradation masterbatch is as follows: The cellulose nanofibrils are treated with oxygen plasma, dispersed in deionized water to form a suspension with a concentration of 3-5 wt%, and freeze-dried to obtain a fiber matrix; Dissolve the algae powder, add glycerol, mix well to obtain an impregnation solution, soak the fiber matrix in the impregnation solution for 2-4 hours, take out, dry, and crush to obtain matrix powder; The base powder is mixed evenly with PHA, a foaming agent and a nucleating agent at 90-100° C., then foamed at 150-160° C. and 15-20 MPa for 5-6 minutes, and then crushed into powder to prepare a degradation masterbatch.

3. The fully biodegradable PE stretch film according to claim 2, characterized in that: Polylactic acid fiber, sodium lauryl sulfate and gum arabic are also added to the suspension, which is evenly stirred and then freeze-dried. The mass ratio of the polylactic acid fiber, sodium lauryl sulfate, gum arabic and cellulose nanofibrils is 0.3-0.4:0.28-0.3:1.9-2:

1.

4. The fully biodegradable PE stretch film according to claim 3, characterized in that: The polylactic acid fiber is made by the following method: Dispersing diatom frustules and carboxymethylated Tremella fuciformis polysaccharide in DMF, ultrasonically dispersing at 60-75° C. for 3-5 hours, filtering, washing, and drying to obtain modified diatom frustules; The polylactic acid resin and the modified diatom frustules are uniformly mixed and melt-spun to obtain polylactic acid fibers, wherein the mass ratio of the polylactic acid resin to the diatom frustules and the carboxymethylated tremella polysaccharide is 1:0.05-0.1:0.1-0.

2.

5. The fully biodegradable PE stretch film according to claim 1, characterized in that: The opening agent is porous starch, and the preparation method of the porous starch is as follows: Starch, pectin, water and microcrystalline cellulose are mixed in a mass ratio of 80-90:2-4:45:5, kneaded at 90-95°C for 10-15 minutes to obtain a composite, kept at 160-165°C and 18-20MPa for 5-6 minutes, released the pressure, and crushed to obtain a foaming intermediate; The foaming intermediate is dispersed in acetonitrile to form an emulsion with a concentration of 1.5-2wt%, succinic acid is dispersed in acetonitrile, heated and stirred to dissolve, added to the emulsion, heated to 75-80°C, kept warm for 20-24h, cooled to 60-65°C, filtered, washed, and dried at 120-125°C. The mass ratio of the foaming intermediate to succinic acid is 1:2.5-3.

6. The fully biodegradable PE stretch film according to claim 1, characterized in that: The density of the LDPE is 0.924 g / cm 3 , melt index is 1.9g / 10min; The density of the MLLDPE is 0.918 g / cm 3 , the melt index is 1g / 10min.

7. The fully biodegradable PE stretch film according to claim 1, characterized in that: The foaming agent is selected from at least one of azodicarbonamide, sodium bicarbonate and zinc oxide; The nucleating agent is selected from at least one of boron nitride, lignin and calcium carbonate.

8. The fully biodegradable PE stretch film according to claim 1, characterized in that: The thickness ratio of the outer layer, the middle layer and the inner layer is 3:4:

3.

9. The fully biodegradable PE stretch film according to claim 1, characterized in that: The lubricant is selected from polyethylene wax or oleic acid amide; The biodegradable tackifying masterbatch is selected from at least one of rosin resin, polymerized rosin, disproportionated rosin, rosin glycol ester, rosin glycerol ester, rosin pentaerythritol ester, terpene resin, polymerized terpene, and terpene-styrene resin.

10. A process for preparing the fully biodegradable PE wrapping film according to any one of claims 1 to 9, characterized in that: The following steps are involved: The outer layer material is prepared by mixing, melting, extruding and granulating the raw materials for the outer layer in the formula amount, the middle layer material is prepared by mixing, melting, extruding and granulating the raw materials for the middle layer in the formula amount, and the inner layer material is prepared by mixing, melting, extruding and granulating the raw materials for the inner layer in the formula amount; The outer layer material, the middle layer material and the inner layer material are mixed according to a proportion, and then melt-cast into a film, and the melting temperature is 180-200°C.

Citation Information

Patent Citations

  • Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) foaming material and preparation method thereof

    CN104448745A

  • Degradable foaming package material and preparation method thereof

    CN107418169A

  • Stretching and wrapping film for machine and preparation method of stretching and wrapping film

    CN115923290A

  • Micro-foaming biodegradable film and preparation method thereof

    CN116285239A

Cited By

  • Recyclable POF heat shrink film and preparation method thereof

    CN120534039A